Synthesis of Phosphate Ethanolamide Derived from Free Fatty Acids of Cooking Oil Processing From Crude Palm Oil. (Talenta Publisher, 2021)
Synthesis of Phosphate Ethanolamide Derived from Free Fatty Acids of Cooking Oil Processing From Crude Palm Oil.